2021
DOI: 10.1002/cjoc.202100633
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule: Polymer Blends for N‐type Organic Thin Film Transistors via Bar‐coating in Air

Abstract: Fabricating n-type organic thin film transistors (OTFTs) based on small molecules via solution processing under atmospheric condi-Keywords Organic thin-film transistors | Thin films | Electron transport | Blend materials | Solvent effects 92 www.cjc.wiley-vch.de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In some studies, the addition of polymers to increases the viscosity of the solution and suppress the dewetting behavior of small molecules can better meet the demand of crystal growth. [163][164][165][166] Pisula and co-workers [167] doped PMMA into the dip coating solution of α,ω-dihexylquaterthiophene (DH4T). They found that with the increase of mass fraction and molecular weight of PMMA, the DH4T crystal grew up, and the corresponding device mobility also improved significantly (Figure 13a-d).…”
Section: Supplementation Of Solutesmentioning
confidence: 99%
“…In some studies, the addition of polymers to increases the viscosity of the solution and suppress the dewetting behavior of small molecules can better meet the demand of crystal growth. [163][164][165][166] Pisula and co-workers [167] doped PMMA into the dip coating solution of α,ω-dihexylquaterthiophene (DH4T). They found that with the increase of mass fraction and molecular weight of PMMA, the DH4T crystal grew up, and the corresponding device mobility also improved significantly (Figure 13a-d).…”
Section: Supplementation Of Solutesmentioning
confidence: 99%
“…The introduction of electron‐withdrawing groups (EWGs), such as fluorine (F), [ 9‐16 ] cyano (CN), [ 17‐20 ] imide, [ 12,21‐24 ] amide, [ 21,25‐26 ] and carbonyl (C=O) [ 27 ] groups in building blocks is a common strategy to lower the HOMO and LUMO levels of CPs. Many building blocks containing F atom(s) have been reported for the synthesis of high‐performance n‐type or ambipolar conjugated polymers.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…As an emerging material candidate for next‐generation light sensing, organic semiconductors can compensate well for the shortages of the traditional inorganic photodetectors for fabricating high‐performance NIR photodetectors, owing to their advantages of lightweight, low toxicity, solution processability, excellent mechanical flexibility, high energy gap tunability, capability of monolithic integration, etc . [ 15‐17 ] In addition, organic photodetectors can be operated at room temperature, avoiding the use of a cooling system. [ 18 ] With these attractive advantages, NIR organic photodetectors have demonstrated a wide range of applications including spectrum analyzers, [ 19 ] artificial retinal implants, [ 20 ] and spectroscopic image sensing, [ 21 ] as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%